RELATIONSHIP OF ACCOUNTANTS AND LAWYERS IN TAX PRACTICE. - Carey, John L. (The Accounting Review, 1951)
This article focuses on the relationship of accountants and lawyers in Tax practice. The American Bar Association's committee on unauthorized practice of law first turned its attention to the activities of accountants in connection with tax matters about 1932. From that time there has been some reference to accountants in almost every annual report of the committee. The first meeting of representatives of the American Institute of Accountants and the American Bar Association took place in 1932. The principal question at issue at that time was whether certified public accountants should be permitted to continue to practice before the U.S. Board of Tax Appeals. In the spirit which these words exemplify it should be possible for the two professions of law and accounting to adjust any and all differences by friendly negotiation, provided that the most enlightened and objective minds in the two professions will address themselves to the task. Many of these minds will be found in the faculties of the law schools and the accounting faculties of the schools of business. The author believes that they have an opportunity to make a great contribution to an enduring solution of a problem which is of vital importance, not only to their own professions, but to the taxpayers of the nation and to the Federal government, which depends upon income taxes for so large a proportion of its revenues.